2023
DOI: 10.1038/s41467-023-39447-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Transcriptomics-correlated Electron Microscopy maps transcriptional and ultrastructural responses to brain injury

Abstract: Understanding the complexity of cellular function within a tissue necessitates the combination of multiple phenotypic readouts. Here, we developed a method that links spatially-resolved gene expression of single cells with their ultrastructural morphology by integrating multiplexed error-robust fluorescence in situ hybridization (MERFISH) and large area volume electron microscopy (EM) on adjacent tissue sections. Using this method, we characterized in situ ultrastructural and transcriptional responses of glial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Quantification of Ccn1 + astrocytes relative to vehicle (PBS) (n=5-6 mice/group). j , spatial transcriptomic analysis correlating regions of LPC-demyelinated corpus callosum with Ccn1 + astrocytes and microglia exhibiting a WDM molecular profile 67 . k , Ccn1 + astrocytes (white arrowheads) intermingle with IBA1 + microglia/macrophages nodules (yellow arrowheads) neighboring mouse MOG 35-55 EAE spinal cord white matter lesions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of Ccn1 + astrocytes relative to vehicle (PBS) (n=5-6 mice/group). j , spatial transcriptomic analysis correlating regions of LPC-demyelinated corpus callosum with Ccn1 + astrocytes and microglia exhibiting a WDM molecular profile 67 . k , Ccn1 + astrocytes (white arrowheads) intermingle with IBA1 + microglia/macrophages nodules (yellow arrowheads) neighboring mouse MOG 35-55 EAE spinal cord white matter lesions.…”
Section: Resultsmentioning
confidence: 99%
“…9 e-g). We also interrogated astrocyte Ccn1 expression and molecular indicators of the WDM state from a recently published spatial transcriptomics dataset from lysolecithin demyelination in the mouse brain 67 . Here we determined, once again, that Ccn1 + astrocytes and WDM microglia are intimately associated in demyelinated regions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the numerous advantages offered by recent techniques, the main hurdle in studying cellular interactions is to accurately identify the relevant cellular populations that shape the injured environment. While available stRNA-seq methods retain spatial information, they either lack the cellular resolution required to identify single cells 64 or are restricted to a subset of the transcriptome, introducing bias in data interpretation 65 . Conversely, several studies based on the scRNA-seq failed to associate the identified clusters to the injury because spatial information about clusters was lost 66 .…”
Section: Discussionmentioning
confidence: 99%
“…61 Additionally, harnessing the high spatial resolution on structure afforded by the TEM, one can also correlate structural information with spatial transcriptomics approaches. 62 Brillouin Microscopy. Brillouin microscopy (BM) has recently emerged as a powerful and versatile technique for studying the mechanical properties of diverse biological samples.…”
Section: Part 1: Imaging-based Techniquesmentioning
confidence: 99%
“…Some correlative approaches are being developed to combine the advantages of different techniques, such as with optical microscopy techniques like cryo-correlative light and electron microscopy (cryo-CLEM) . Additionally, harnessing the high spatial resolution on structure afforded by the TEM, one can also correlate structural information with spatial transcriptomics approaches …”
Section: Part 1: Imaging-based Techniquesmentioning
confidence: 99%